2022
DOI: 10.1177/14780771221134958
|View full text |Cite
|
Sign up to set email alerts
|

Optimization-aided design: two approaches for reflective exploration of design search space

Abstract: The role of using performance-based design optimization in early-stage architectural design to prevent poorly designed buildings has been increasingly recognized by researchers and designers. Recently, a large amount of research has been made focusing on technical advancement, which, however, also reflects the limited research on how this technique can be applied to the design process and how it can aid designers when confronting ill-defined design problems. In this regard, this paper centers on the design app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…In addition, two different design exploration approaches relevant to the use of EvoMass were also introduced (Fig. 2), including parallel and iterative design exploration (Wang, 2022). The two approaches are abstracted and modeled from the previous EvoMass applications and can become the reference for students using the system and conducting the design exploration.…”
Section: Teaching Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, two different design exploration approaches relevant to the use of EvoMass were also introduced (Fig. 2), including parallel and iterative design exploration (Wang, 2022). The two approaches are abstracted and modeled from the previous EvoMass applications and can become the reference for students using the system and conducting the design exploration.…”
Section: Teaching Methodsmentioning
confidence: 99%
“…As using the system does not require scripting, only one tutorial was focused on the technical issues related to establishing the system workflow. Another three tutorials were focused on: 1) the operations of the EvoMass Generator components for design generation, 2) the operation Figure 1 The main viewer of the system Figure 2 Two design exploration approaches for EvoMass application (Wang, 2022) of the grasshopper Evolver component for computational (evolutionary) optimization, and 3) the operations of the cloud evaluation server for design evaluation. The last tutorial focused on how to conduct optimization-based design exploration using different performance factors and design directions.…”
Section: Teaching Methodsmentioning
confidence: 99%
“…10 In this case study, the default control parameter setup is used, whereas when using EvoMass, it also allows designers to define different control parameters to generate buildings with different formal characteristics. 20 As a result, with different formal characteristics, the produced designs from the optimization will be different, which may further richen the information feedback from different design aspects. However, investigating the impact of different parametric setups is beyond the scope of this study, which was also demonstrated in a prior study.…”
Section: Demonstrationmentioning
confidence: 99%
“…More recently, a few studies have been conducted focusing on integrating computational design optimization into early-stage design exploration and design development processes (Janssen et al, 2022;Wang, 2022). In these studies, designers are assumed to conduct multiple optimization runs with different parametrized design strategies, in order to compare their strengths and weaknesses.…”
Section: Computational Optimization For Architectural and Urban Designmentioning
confidence: 99%
“…However, this application paradigm also limits the usage of computational design optimization in early design stages. Early-stage design often involves parallel exploration and comparison of multiple alternative design strategies, such as building typologies (Xu et al, 2019), building façade schemes (Wang, Zhang, et al, 2022), and building formal characteristics (Wang, 2022). In this regard, incorporating computational design optimization into such parallel design exploration processes can further enhance its practical utility in architectural and urban design.…”
Section: Introductionmentioning
confidence: 99%